About the dialectical historiography of international law. Issue 1 (1st September 2016) - Hunter, Ian
ABSTRACT: Currently there is a widely held view that international law and its historiography did not emerge until the nineteenth century, with earlier forms of jus gentium or Völkerrecht being consigned to the status of a superseded 'pre-history'. It is not widely understood that this view itself belongs to a particular kind of historiography – the dialectical historiography of international law – that was born in 1840s Germany, and wielded this viewpoint as a cultural-political weapon to exclude its rivals from 'modernity'. In outlining a history of this dialectical historiography, the present article focuses on the reception of Kantian and Hegelian philosophies, understood as species of Protestant rationalist metaphysics, in the juridical-political arena of the German Vormärz . Dialectical histories and theories of international law were the effects and instruments of this reception, which gave rise to the new academic subculture of philosophical international law. This subculture in turn permitted the fashioning of a new intellectual persona, the philosopher-jurist, who could claim to transcend positive treaty-based international law through personal insight into a 'common international legal consciousness', and to treat this insight as the threshold of 'modern' international law.